Nova Turco-Samoiedica - Ünal, Orçun (Finnisch-Ugrische Forschungen, 2023)
The present paper focuses on the lexical contact between Turkic and Samoyedic and discusses nine new possible Turkic loanwords in Proto-Samoyedic and eight new possible Samoyedic loanwords in Turkic. The introduction offers a modest bibliography of the scattered studies on the subject. Two of the new Turkic loanwords in Proto-Samoyedic suggest that they reached the recipient language through the mediation of Yeniseian languages.